Shear Strength Optimization of Laser-Joined Polyphenylene Sulfide-Based CFRTP and Stainless Steel - Sheng, L.Y.; Wang, F.Y.; Wang, Q.; Jiao, J.K. (Проблемы прочности, 2018)
A thermosetting plastic and stainless steel were joined by the fiber laser with and without polyphenylene sulfide (PPS) additive. Its microstructure, interface morphology, and shear strength were investigated.